Quality control in automotive industry - Wan Nur Ain Ruzana, Wan Ibrahim (2014)
This thesis is focusing on the level of awareness of Quality Control (QC) among the workers in the automotive industry. The implemented of Quality Control (QC) will different in each industry. The Quality Control (QC) plays a fundamental role in determining the performance in automotive industries. In automotive industry Quality Control (QC) is a process through industry by companies to ensure that product quality is maintained or improved and manufacturing errors are reduced or eliminated. Quality Control is one of the process inspection and auditing to maintain the quality and legal standards to achieve the level of standard. This study was mainly carried out by preparing the letter to industry and do survey by distributed questionnaire, data collection, analysis of the data, result and discussion of the analysis, and conclusion. Finally, it is hope that the results from the study could contribute to the researcher for future improvement